Ethenolysis: A Green Catalytic Tool to Cleave Carbon–Carbon Double Bonds. Issue 35 (30th June 2016) - Bidange, Johan; Fischmeister, Cédric; Bruneau, Christian
Abstract: Remarkable innovations have been made in the field of olefin metathesis due to the design and preparation of new catalysts. Ethenolysis, which is cross‐metathesis with ethylene, represents one catalytic transformation that has been used with the purpose of cleaving internal carbon–carbon double bonds. The objectives were either the ring opening of cyclic olefins to produce dienes or the shortening of unsaturated hydrocarbon chains to degrade polymers or generate valuable shorter terminal olefins in a controlled manner. This Review summarizes several aspects of this reaction: the catalysts, their degradation in the presence of ethylene, some parameters driving their productivity, the side reactions, and the applications of ethenolysis in organic synthesis and in potential industrial applications. Abstract : A green C=C cleavage : Ethenolysis, which is cross‐metathesis with ethylene, is a catalytic transformation that has been used to cleave internal carbon–carbon double bonds, with objectives that include the ring opening of cyclic olefins to produce dienes and the shortening of unsaturated hydrocarbon chains to degrade polymers or generate valuable shorter terminal olefins in a controlled manner.